Pendapatan Asli Daerah dan Dana Perimbangan terhadap Kinerja Keuangan Pemerintah Daerah - Alkansa Fadila Ramadani; Muslimin Muslimin (IPM2KPE, 2022)
This study aims to determine the effect of PAD and Balancing Funds on the financial performance of local governments. This research method is descriptive quantitative. This research utilizes the Non-Probability Sampling method as well as the saturated sampling technique. The type of data used is secondary data obtained from the 2016-2020 Kediri City Government Budget Realization Report. The data were analyzed using multiple linear regression analysis with the help of SPSS 25 software. The results showed that PAD had a positive effect on local government financial performance. Meanwhile, the Balancing Fund has no effect. However, PAD and the Balancing Fund together have a significant effect on the local government's financial performance. In conclusion, the higher the PAD, the better the local government's financial performance, and the amount of balancing funds does not affect the regional government's financial performance. However, on the other hand, PAD and the Balancing Fund together have a significant impact on the local government's financial performance. Keywords: Balancing Fund, Regional Financial Performance, Regional Original Income